Pengaruh Kualitas Pelayanan dan Kualitas Produk Terhadap Ulasan Pelanggan pada Mie Gacoan Cabang Solo Veteran - Muzazanah, Siti; Fadhillah, Is (As-Syirkah: Islamic Economic & Financial Journal, 2024)
Indonesia is a country with a variety of cultures, customs, regional languages ​​and food which has different characteristics in each region. Various culinary delights have become an attraction for local and foreign tourists. Seeing this huge interest and potential, it has aroused people's interest in trying businesses in the culinary sector. Mie Gacoan is one of Indonesia's culinary businesses that is growing and spread across various regions. By having a unique menu name at the beginning of its opening, Mie Gacoan succeeded in attracting many consumers with its flagship menu, namely spicy noodles with adjustable levels of spiciness and selling other products in the form of dim sum and various kinds of drinks. This research aims to determine the influence of service quality and product quality on customer reviews of Mie Gacoan at the Solo Veteran branch. Data collection in this research used a questionnaire containing 12 questions which were distributed to 126 respondents who were Mie Gacoan Solo Veteran customers. With questions and statements related to the variables being studied, namely the influence of service quality and product quality on customer reviews of Mie Gacoan Solo Veteran Branch. The method used in this research uses quantitative methods.  Sampling used a non-purposive sampling technique with respondents who currently reside in the Greater Solo area and have made purchases at Mie Gacoan Solo Veteran Branch. The results of the analysis on the t test of the service quality variable have a significance value of 0.106 which is greater than 0.05 with a calculated t value of 1.629, so it can be said that the service quality variable has no effect on the review variable. Meanwhile, the value of the product quality variable is the calculated t and t table values ​​or 6.359 > 1.661. Apart from that, it is known that the significance of X2 to Y is 0.00, which means it is smaller than 0.05. So it is concluded that there is a significant influence between product quality on the reviews that customers will give to Mie Gacoan Solo Veteran Branch.